Computational evaluation of Mg-decorated g-CN as clean energy gas storage media. (14th October 2021) - Chen, Xihao; Li, Ji-wen; Dou, Xilong; Gao, Peng
Abstract: Ab initio studies were conducted to evaluate the performance of hydrogen storage by Mg-decorated graphite carbon nitride (g-CN, heptazine structure). In our calculations, we found that each unit of this material can accommodate one Mg atom. Partial charges from Mg were transferred to the pristine material, making itself more electropositive. This is favorable for hydrogen storage, as the adsorbed H2 molecules can be easily polarized, and the electrostatic interactions can be enhanced. The configurations of the Mg-decorated g-CN with multiple adsorbed H2 molecules were presented in this study, and the related adsorption mechanisms were also discussed in details. Each unit can adsorb at most 7 H2 molecules with adsorption energies ranging from −0.276 eV to −0.130 eV. In addition, besides Mg, we also noticed that the nitrogen atoms also perform well in hydrogen adsorption. For this novel material, its highest capacity of hydrogen storage can reach to 7.8 wt%, highly surpassing the target value of 5.5 wt% set by the U.S. department of energy (DOE)[1]. The computational results provided in this study indicates a promising prospect for alkali metal functionalized 2D materials in energy storage; and through decent explorations, the performance of this class of materials can be largely improved. Graphical abstract: Image 1 Highlights: Metal Mg was applied to decorate monolayer g-CN. The Mg-decorated g-CN shows good performance in hydrogen storage. Electronic structure of this material was solved via DFT calculations.